Preoperative embolization of intracranial meningiomas. - Manelfe, C; Lasjaunias, P; Ruscalleda, J (American Journal of Neuroradiology, 1986)
The goal of preoperative embolization of intracranial meningiomas is to facilitate their surgical removal by reducing tumor vascularity and decreasing blood loss during surgery. This study is based on personal experience with about 100 embolized meningiomas and on the experience of others. Embolization is performed during the same session as diagnostic angiography. The appropriate embolic materials (absorbable or nonabsorbable) are chosen according to the location of the tumor, the size of the feeding arteries, the blood flow, and the presence of any potentially dangerous vessels (dangerous anastomoses between external carotid artery and internal carotid or vertebral arteries, arteries supplying the cranial nerves). Preoperative embolization appeared to be very useful in large tumors with pure or predominant external carotid artery supply (convexity meningiomas), in skull-base meningiomas, and in middle fossa and paracavernous meningiomas. It was also useful in falx and parasagittal meningiomas receiving blood supply from the opposite side and in posterior fossa meningiomas. CT low densities demonstrated after embolization did not always correlate with necrosis on microscopic examination, and large areas of infarction could be found despite normal CT. Embolic material was found on pathologic examination in 10%-30% of cases; fresh or recent ischemic and/or hemorrhagic necrosis consistent with technically successful embolization was demonstrated in 40%-60% of cases. With careful technique complications are rare.